The effects of copper doping on morphology and room-temperature photoluminescence of ZnO nanocolumns. Issue 50 (15th November 2022) - Blount, Parker; Marder, Lauren; Oyegoke, Jamal; Trad, Tarek
Abstract : In this study, a versatile vapor phase transport method for the synthesis and copper-doping of ZnO nanocolumns is demonstrated. Abstract : In this study, a versatile vapor phase transport method for the synthesis and copper-doping of ZnO nanocolumns is demonstrated. Doping percentage (up to 5%) showed no effect on the wurtzite structural phase of ZnO nanocolumns. However, a decrease in nanocolumn diameter (cross-sectional length of longest side or diagonal) due to doping was observed by scanning electron microscopy. Reduced rate of electron–hole recombination was inferred from a decrease in the intensity of the near-band edge emission peak shown in room-temperature photoluminescence spectra. Expression of structural defects in both doped and undoped nanocolumns suggest p-type conductivity. Observed copper-doping effects show promise for utilizing such structures as electrode components in dye-sensitized solar cells.